Studies Regarding Some Phenotype Parameters and the Evolution of Shepherd Dog Breeds in Romania - Adrian Marcu; Adela Marcu; Cornelia Vintilă; Dorel Dronca; Daniela Radu (Scientific Papers Animal Science and Biotechnologies, 2023)
Now days, Romania have three dog breeds homologated by FCI (Federation Chynologique Internationale): Romanian Mioritic Shepherd Dog, Romanian Charpatian Shepherd Dog and Southeastearn European Shepherd Dog. The fourth breed, Romanian Shepherd Dog Corby is in homologation. It was studied the evolution of the population and two phenotype parameters (weight and wither height) at the Romanian shepherd dogs. The first three breeds have a good homogenity and a positive numeric evolution. Romanian Shepherd Dog Corby are less homogene and the selection process must be improve.